Die Wasserwanzenfauna eines Moorgebietes in Mecklenburg (Heteroptera: Corixoidea, Notonectoidea, Gerroidea). - Schieferdecker, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The author determined 32 species of water-bugs in moor waters of the wild-life preserve "East shore of Müritz" and makes an ecological assessment. A number of northern species living in the North German Lowland prefer moors and may be called moorloving. Euryoecic species were found, too, but often with lower numbers of individuals. A few species seem to be averse to moors. So far neither southern and south-eastern species nor western, Atlantic species have been found in the area under examination.